Airway complications after lung transplantation: Perioperative risk factors and clinical outcomes - Siddhartha G. Kapnadak, MD; Kathleen J. Ramos, MD, MS; Rachel Flodin, MS; Sanaa Mansoor, MD; Kyle Bilodeau, MD; Peter Beidler, BS; Erika D. Lease, MD; Ryan Thomas, BS; Richard Dubois, MD; Jay Pal, MD, PhD; Michael S. Mulligan, MD (JHLT Open)
Background: Airway complications after lung transplantation are common and contribute to worse outcomes. There are limited data documenting perioperative risk factors that could be mitigated to reduce risk. Our objectives were to (1) assess the impact of pretransplant disease–modifying medications and post-transplant hypotension, hypovolemia, and mechanical ventilation on the risk of airway complications; (2) evaluate the association of airway complications with post-transplant lung function and survival. Methods: One hundred and forty-five bilateral lung transplant recipients at our center were included. Demographics, pretransplant medications, post-transplant intensive care unit variables, and lung function were compared between recipients who did vs did not develop airway complications. Post-transplant survival was estimated using Kaplan-Meier analysis. Results: Forty-eight (33.1%) recipients (75% male) developed airway complications. There were no significant associations in pretransplant exposure to prednisone (including by dose), other immunosuppressants, or antifibrotics, alone or in any combination, with the development of airway complications. There were no differences in ventilation pressures, but recipients with airway complications had higher peak vasopressor-inotropic scores (18.0 vs 13.0, p = 0.021), lactate levels (9.1 vs 6.8, p = 0.017), need for hemodialysis (22.9% vs 10.3%, p = 0.042), and net fluid balance at 48 hours (10.6 vs 8.9 liters, p = 0.028), respectively, compared to those without. Airway complications were associated with significantly worse survival (HR 2.74 [95% CI 1.35, 5.55], p = 0.004) and lung function (peak forced expiratory value in 1 second 74.8% vs 86.3% predicted, respectively, p = 0.013). Conclusions: Postoperative hypotension and hypoperfusion are associated with increased risk for airway complications after lung transplantation. Airway complications are associated with poor outcomes, and further studies are needed to delineate risk-mitigation strategies.